Antioxidant vitamins and lysophospholipids are critical for inducing mouse spermatogenesis under organ culture conditions. Issue 7 (31st May 2020) - Sanjo, Hiroyuki; Yao, Tatsuma; Katagiri, Kumiko; Sato, Takuya; Matsumura, Takafumi; Komeya, Mitsuru; Yamanaka, Hiroyuki; Yao, Masahiro; Matsuhisa, Akio; Asayama, Yuta; Ikeda, Kazutaka; Kano, Kuniyuki; et al.
Abstract: In vitro mouse spermatogenesis using a classical organ culture method became possible by supplementing basal culture medium with only the product of bovine serum albumin purified by chromatography (AlbuMAX), which indicated that AlbuMAX contained every chemical factor necessary for mouse spermatogenesis. However, since the identity of these factors was unclear, improvements in culture media and our understanding of the nutritional and signal substances required for spermatogenesis were hindered. In the present study, chemically defined media (CDM) without AlbuMAX was used to evaluate each supplementary factor and their combinations for the induction of spermatogenesis. Similar to in vivo conditions, retinoic acid, triiodothyronine (T3 ), and testosterone (T) were needed. Based on differences in spermatogenic competence between AlbuMAX, fetal bovine serum, and adult bovine serum, we identified α‐tocopherol, which strongly promoted spermatogenesis when combined with ascorbic acid and glutathione. Differences were also observed in the abilities of lipids extracted from AlbuMAX using two different methods to induce spermatogenesis. This led to the identification of lysophospholipids, particularly lysophosphatidylcholine, lysophosphatidic acid, and lysophosphatidylserine, as important molecules for spermatogenesis. New CDM formulated based on these results induced and promoted spermatogenesis as efficiently as AlbuMAX‐containing medium. In vitro spermatogenesis with CDM may provide a unique experimental system for research on spermatogenesis that cannot be performed in in vivo experiments.